2011
DOI: 10.1007/s00421-011-2047-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous neuromuscular electrical stimulation: influence of electrode positioning and stimulus amplitude settings on muscle response

Abstract: The aim of the study was to investigate the influence of two different transcutaneous neuromuscular electrical stimulation procedures on evoked muscle torque and local tissue oxygenation. In the first one (MP mode), the cathode was facing the muscle main motor point and stimulus amplitude was set to the level eliciting the maximal myoelectrical activation according to the amplitude of the evoked electromyogram (EMG); in the second one (RC mode), the electrodes were positioned following common reference charts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…Motor point stimulation as a sine qua non-condition to optimize NMES use Gobbo et al (2011) provided convincing evidence on the importance of motor point determination to minimize current intensity and discomfort, and to maximize the muscular tension evoked by NMES. They also used near infrared spectroscopy, which is a technique particularly suitable for investigating local metabolic changes of stimulated muscles (Muthalib et al 2009), and were able to demonstrate that, besides contractile activity, muscle oxygen consumption and hyperaemia were significantly increased when motor point location was carefully determined with a pen electrode rather than being inferred from several legally marketed motor point charts.…”
Section: Nmes Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Motor point stimulation as a sine qua non-condition to optimize NMES use Gobbo et al (2011) provided convincing evidence on the importance of motor point determination to minimize current intensity and discomfort, and to maximize the muscular tension evoked by NMES. They also used near infrared spectroscopy, which is a technique particularly suitable for investigating local metabolic changes of stimulated muscles (Muthalib et al 2009), and were able to demonstrate that, besides contractile activity, muscle oxygen consumption and hyperaemia were significantly increased when motor point location was carefully determined with a pen electrode rather than being inferred from several legally marketed motor point charts.…”
Section: Nmes Methodologymentioning
confidence: 99%
“…They also used near infrared spectroscopy, which is a technique particularly suitable for investigating local metabolic changes of stimulated muscles (Muthalib et al 2009), and were able to demonstrate that, besides contractile activity, muscle oxygen consumption and hyperaemia were significantly increased when motor point location was carefully determined with a pen electrode rather than being inferred from several legally marketed motor point charts. We recommend that the procedure described by Gobbo et al (2011), which is completed in less than a minute, should be consistently incorporated in both clinical and research contexts to optimize NMES application. Botter et al (2011) investigated the uniformity of the muscle motor point location in the lower limb of healthy subjects and found different motor points innervating different portions of the quadriceps, posterior thigh, and tibialis anterior muscles.…”
Section: Nmes Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…St-Pro Multichannel Programmable Neuromuscular Stimulator, LiSin, Turin, Italy). The stimulation return electrode (anode: 130 × 100 mm) was positioned at the third distal of the leg, whereas the stimulation electrode (cathode: 90 × 40 mm) was placed over the most proximal motor point of the GM muscle [20]. A set of brief 2 Hz stimulations of increasing amplitude was administered to determine the maximum compound motor unit stimulus (M-wave).…”
Section: Experimental Procedures and Measurementsmentioning
confidence: 99%
“…Several authors have demonstrated the influence of stimulation parameters, such as electrode positioning, 20 current frequency, 38,44,[53][54][55] current amplitude (intensity), 8,22,44 stimulus pulse duration, 22,23 and burst duty cycle of medium-frequency alternating current, 33,37,55 on electrically induced torque. Burst duty cycle is an important parameter of NMES, as it can directly affect torque production and sensory discomfort in healthy, untrained individuals.…”
Section: T T Conclusionmentioning
confidence: 99%